Total Synthesis of Hapalindole‐Type Natural Products1. (10th October 2014) - Lu, Zhaohong; Yang, Ming; Chen, Pengxi; Xiong, Xiaochun; Li, Ang
Abstract A unified and bioinspired oxidative cyclization strategy was used in the first total syntheses of naturally occurring 12‐epi‐hapalindole Q isonitrile, hapalonamide H, deschloro 12‐epi‐fischerindole I nitrile, and deschloro 12‐epi‐fischerindole W nitrile, as well as the structural revision of the latter. Hapalindoles H and Q were also synthesized.